(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2005)
Let T be a nonnegative random variable representing the lifetimes of individuals in some population. Let f(t) denote the probability density function of T and F(t) denote the distribution function of T, the hazard function of T defined as : If equation (1) integrated we have cumulative hazard function H (t). This paper describes application of kernel method for estimation of hazard function h (.) based censoring data. And then we will show that the hazard estimator is unbiased asymptotically, consistent, and normal asymptotically.